EFEKTIVITAS PERATURAN DAERAH NOMOR 20 TAHUN 2009 TENTANG PEMELIHARAAN TERNAK DI KABUPATEN KEPULAUAN SELAYAR PERSPEKTIF HUKUM ISLAM - Wijaya, Febri Ainul; Hasan, Hamzah; Sohrah, Sohrah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2023)
The existence of wild animals in Selayar Islands Regency reaps various polemics, ranging from disturbances of order, public comfort, destruction of agricultural land and destruction of public facilities. This study aims to determine how effective Regional Regulation Number 20 of 2009 concerning Livestock Rearing in Selayar Island Islamic Law Perspective. The type of research used is descriptive qualitative, with normative juridical and syar'i approaches. The results showed that Regional Regulation Number 20 of 2009 has not been implemented optimally in carrying out supervision and control of wild livestock due to lack of public awareness and government indecision in implementing sanctions for livestock owners. Islam allows keeping livestock for the purpose of obtaining benefits, but it is also expressly stipulated that every farmer is obliged to keep and care for his pets to prevent damage (inconvenience) caused by pets.